2007
DOI: 10.1109/tits.2006.888598
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Vehicle Lateral Dynamics Using a Bifurcation Analysis

Abstract: Issues of stability and bifurcation phenomena in vehicle lateral dynamics are presented. Based on the assumption of constant driving speed, a second-order nonlinear lateral dynamics model is obtained. Local stability and existence conditions for saddle-node bifurcation appearing in vehicle dynamics with respect to the variations in front wheel steering angle are then derived via system linearization and local bifurcation analysis. Bifurcation phenomena occurring in vehicle lateral dynamics might result in spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 17 publications
(32 reference statements)
0
32
0
Order By: Relevance
“…Time-Invariant Case 1) Pure-slip model: The stability of the linear part of the system (16) with the pure-slip time-invariant assumption, i.e, constant longitudinal velocity u, can be addressed with the Hurwitz criterion on the state matrix A in (17). Having negative eigenvalues yields mχ 2 u 2 > mχ…”
Section: Stability Of the Pure And Combined Slip Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Time-Invariant Case 1) Pure-slip model: The stability of the linear part of the system (16) with the pure-slip time-invariant assumption, i.e, constant longitudinal velocity u, can be addressed with the Hurwitz criterion on the state matrix A in (17). Having negative eigenvalues yields mχ 2 u 2 > mχ…”
Section: Stability Of the Pure And Combined Slip Modelsmentioning
confidence: 99%
“…In other words, the system (46) may be stable while A s (ω) is unstable. To find a physical condition (interpretation) for the current time-varying linear lateral models (17) and (36) similar to the condition (4) in the 2DOF bicycle model, the stability of the symmetric A s (ω) =…”
Section: B Quadratic Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Such a bifurcation phenomenon might result in the spin of a vehicle as steering angle changes. The application of bifurcation theory to engineering problems have been well exploited in the recent years (e.g., [10][11][12]). A theoretical analysis of vehicle dynamics has been obtained by applying the bifurcation theory [10], which revealed that the uncontrolled version of vehicle's lateral dynamics might undergo a stationary saddle-node bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…The application of bifurcation theory to engineering problems have been well exploited in the recent years (e.g., [10][11][12]). A theoretical analysis of vehicle dynamics has been obtained by applying the bifurcation theory [10], which revealed that the uncontrolled version of vehicle's lateral dynamics might undergo a stationary saddle-node bifurcation. In addition, the controllability and direct state feedback control laws were also proposed in [13] to stabilize the bifurcation points.…”
Section: Introductionmentioning
confidence: 99%